Top 10 most cited authors in heritage-4th industrial revolution research (2016–2021) - Agapiou, Athos (My University, 2026)
Top 10 most cited authors in heritage-4th industrial revolution research (2016–2021) (2016–2021) (Alviz-Meza, A., Vásquez-Coronado, M.H., Delgado-Caramutti, J.G. et al. Bibliometric analysis of fourth industrial revolution applied to heritage studies based on Web of Science and Scopus databases from 2016 to 2021. Herit Sci 10, 189 (2022). https://doi.org/10.1186/s40494-022-00821-3)
Keywords: Sciences